Prohibition of Intera Religion Marriage in Indonesia - Sonny Dewi Judiasih; Nazmina Asrimayasha Nugraha; Luh Putu Sudini (Faculty of Law, Universitas Jenderal Soedirman, 2019)
As a country with Pancasila as the philosophy, the first pillar is believing in God the One, therefore marriage is closely related to the issue of religion. Law number 1 in 1974 on Marriage stated that a marriage should be done by two people with the same religion and beliefs. Inter-religion marriage between Indonesian citizens in foreign states violate the regulations found in article 2 paragraph (1) and article 56 paragraph (1) of Law number 1 in 1974 on Marriage. The problems analyzed in this paper are: first, the legal status of inter-religion marriage in law system of Indonesia; and second, inter-religion marriage performed by Indonesian citizens in foreign countries. The research of this paper shown that Indonesia prohibits inter-religion marriage since it violates the principle of “the belief in the one and only God,” which expects marriage to be performed only by a couple who share the same religious belief.Keywords: Indonesia, Inter-religion Marriage, Legitimate Marriage, Marriage Law, Religion